Autopilot Design Method for the Blended Missile Based on Model Predictive Control - Baoqing Yang; Yuyu Zhao (International Journal of Aerospace Engineering)
This paper develops a novel autopilot design method for blended missiles with aerodynamic control surfaces and lateral jets. Firstly, the nonlinear model of blended missiles is reduced into a piecewise affine (PWA) model according to the aerodynamics properties. Secondly, based on the equivalence between the PWA model and mixed logical dynamical (MLD) model, the MLD model of blended missiles is proposed taking into account the on-off constraints of lateral pulse jets. Thirdly, a hybrid model predictive control (MPC) method is employed to design autopilot. Finally, simulation results under different conditions are presented to show the effectiveness of the proposed method, which demonstrate that control allocation between aerodynamic control surfaces and lateral jets is realized by adjusting the weighting matrix in an index function.